Methodology of Connecting the 4Q Intelligences or Reaching Suitable Judgement (Journal of Universal Excellence, 2026)
Research Question (RQ): How to find a system of reasoning (analysis and synthesis) to be able to encompass the wholeness of the phenomenon under study?Purpose: The purpose of this article is to present and analyze an assessment proposal called Connecting Intelligences 4 Q.Method: In the research, we used qualitative methodology, comparative content analysis. The research is analytical, it examines the qualitative experience of the author and supports it with literature from the fields of linguistics, psychoanalysis, neurology and sociology. The method of reasoning is both inductive and deductive.Results: Assessment must be balanced, interdisciplinary and aimed at building integrated assessment models. The proposed solution encourages further research into the concept of judgment and analyzes it at the levels of cognition, emotion and neurology.Organization: The proposal is applicable to both organizations and groups, as it deals with the natural human ability to analyze and synthesize, i.e. the comprehensive ability to judge. Since human engagement is always related to cooperation, connection and communication, the proposed model can be useful and practically applicable.Society: The proposal supports the sustainable development of society, as it deals with key topics that support broader social issues and the ethics of individuals as members of society. At the same time, it shows how we can judge from the levels of mind (IQ), emotion (EQ), spirit (SQ) and body (PQ). It thereby includes interdisciplinarity and gives it a key focus in the assessment.Originality: The proposed solution is interesting, as it connects sociological, anthropological and neurological science. It offers practical ideas and guidance on how to connect levels that are different and how to pave the way to balanced ethical judgment.Limitations/Future Research:  In the research, we focused on the qualitative method with content analysis. However, we recommend concrete models and further research on the assessment itself, both on the cognitive and emotional levels.
Keywords: inteligence; judgement; intrdisciplinarita; perception; method